Using Information Technology and Social Networking for Recruitment of Research Participants: Experience From an Exploratory Study of Pediatric Klinefelter Syndrome - Close, Sharron; Smaldone, Arlene; Fennoy, Ilene; Reame, Nancy; Grey, Margaret (JMIR Publications, 2013)
BackgroundRecruiting pediatric samples for research may be challenging due to parental mistrust of the research process, privacy concerns, and family time constraints. Recruitment of children with chronic and genetic conditions may further complicate the enrollment process. ObjectiveIn this paper, we describe the methodological challenges of recruiting children for research and provide an exemplar of how the use of information technology (IT) strategies with social networking may improve access to difficult-to-reach pediatric research participants. MethodsWe conducted a cross-sectional descriptive study of boys between the ages of 8 and 18 years with Klinefelter syndrome. This study presented unique challenges for recruitment of pediatric participants. These challenges are illustrated by the report of recruitment activities developed for the study. We reviewed the literature to explore the issues of recruiting children for research using conventional and IT approaches. Success rates of conventional recruitment approaches, such as brochures, flyers in medical offices, and physician referrals, are compared with IT-based outreach. The IT approaches included teleconferencing via a Klinefelter syndrome support group, services of a Web-based commercial recruitment-matching company, and the development of a university-affiliated research recruitment website with the use of paid advertising on a social networking website (Facebook). ResultsOver a 3-month period, dissemination of over 150 recruitment brochures and flyers placed in a large urban hospital and hospital-affiliated clinical offices, with 850 letters to physicians and patients were not successful. Within the same period, face-to-face recruitment in the clinical setting yielded 4 (9%) participants. Using Web-based and social networking approaches, 39 (91%) agreed to participate in the study. With these approaches, 5 (12%) were recruited from the national Klinefelter syndrome advocacy group, 8 (19%) from local and teleconference support groups, 10 (23%) from a Web-based research recruitment program, and 16 (37%) from the university-affiliated recruitment website. For the initial 6 months, the university website was viewed approximately 2 to 3 times per day on average. An advertisement placed on a social networking site for 1 week increased website viewing to approximately 63 visits per day. Out of 112 families approached using all of these methods, 43 (38%) agreed to participate. Families who declined cited either travel distance to the study site (15, 22%) or unwillingness to disclose the Klinefelter syndrome diagnosis to their sons (54, 78%) as the reasons for nonparticipation. ConclusionsUse of Web-based technologies enhances the recruitment of difficult-to-reach populations. Of the many approaches employed in this study, the university-affiliated recruitment website supported by a Facebook advertisement appeared to be the most successful. Research grant budgets should include expenses for website registration and maintenance fees as well as online advertisements on social networking websites. Tracking of recruitment referral sources may be helpful in planning future recruitment campaigns.